2021
DOI: 10.1101/2021.12.20.473538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delivery of CAR-T Cells in a Transient Injectable Stimulatory Hydrogel Niche Improves Treatment of Solid Tumors

Abstract: Adoptive cell therapy (ACT) has proven to be highly effective in treating blood cancers such as B cell malignancies, but traditional approaches to ACT are poorly effective in treating the multifarious solid tumors observed clinically. Locoregional cell delivery methods have shown promising results in treating solid tumors compared to standard intravenous delivery methods, but the approaches that have been described to date have several critical drawbacks ranging from complex manufacturing and poor modularity t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Previous work has shown that immune cells can infiltrate into these PNP hydrogel materials when certain types of cargo such as vaccine components are present and that encapsulated therapeutic cells exhibit motility, indicating that an active antibody transport mechanism could be possible. 31,34 It is also possible that biological interactions with the material change its physical properties over time, which could alter its drug release characteristics. 63 Future work should include investigating cellular infiltration into antibody-loaded PNP hydrogels as well as measuring antibody biodistribution beyond the bloodstream, such as the lymphatic system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that immune cells can infiltrate into these PNP hydrogel materials when certain types of cargo such as vaccine components are present and that encapsulated therapeutic cells exhibit motility, indicating that an active antibody transport mechanism could be possible. 31,34 It is also possible that biological interactions with the material change its physical properties over time, which could alter its drug release characteristics. 63 Future work should include investigating cellular infiltration into antibody-loaded PNP hydrogels as well as measuring antibody biodistribution beyond the bloodstream, such as the lymphatic system.…”
Section: Resultsmentioning
confidence: 99%
“…49 Finally, the yield stress of each formulation was determined to assess the ability of the depot to retain its shape under the forces present the site of injection; it has previously been demonstrated that yield stress is an important rheological property for subcutaneous depot formation and retention. 34,50 Yield stresses of 70 and 350 Pa were measured for the 1:5 and 2:10 formulations, respectively (Figure 2e). Again, previous work has shown that increasing nanoparticle content results in higher yield stress values.…”
Section: Rheological Characteristics Of the Pnp Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapy Phase trial Mesothelin-Specific CAR-T cells I CEACAM5-specific CAR-T cells I Because of low invasion of T cells, lack of targeted TME, and unstable expression after injection, CAR-T cells are hindered from infiltrating into the tumor site. A simple and efficient CAR-T delivery method is developed recently by adding CAR-T cells and cytokines into the hydrogel to improve the curative effect on solid tumors [12]. At present, other challenges for CAR-T therapy contain the absence of sustained attack and the evolution of CD19-tumor cells which cannot be recognized.…”
Section: Application Of Car-t Cell Therapymentioning
confidence: 99%
“…For example, the pro-inflammatory cytokine IL-1 and TNF-α polarize macrophages into a pro-inflammatory phenotype, whose overactivation can lead to tissue damage [14]. In addition, while displaying promising results in targeting blood cancers, CAR-T treatments show reduced efficacy against solid tumours [15]. Therefore, CAR-T therapies are still under active research and optimization to minimize side effects.…”
Section: Introductionmentioning
confidence: 99%